Carbon-Silica Composites with Cellulose Acetate, Polyisocyanate and Copper Chloride - Goncharuk, V.V.; Dubrovin, I.V.; Dubrovina, L.V.; Kucheruk, D.D.; Naboka, O.V.; Ogenko, V.M. (Physics and Chemistry of Solid State, 2016)
Cellulose acetate and polyisocyanate copolymer synthesized by simultaneous mixing of cellulose acetate and polyisocyanate with acetone solution of Copper chloride and fumed silicon dioxide was carbonized in a silicon dioxide template. The composite structure and composition was studied with SEM, EDS and XRD. It was shown that the porous carbonaceous nanomaterial was synthesized where formed carbon was represented by coating on silicon dioxide and consisted of graphite, graphene and amorphous nonstructured carbon. Crystals of metallic copper with the size up to few µm were formed from Copper chloride after reduction of Cu2+ with products of organic compounds pyrolisis.